Does Insurance Status Influence Outpatient Flow? Cross-Sectional Comparison of Insured and Uninsured Patients in a Tertiary Hospital in Nigeria. (March 2022) - Opurum, Ndubuisi E.; Kemdirim, Chinonye J.; Uduak, Abasianam; Hart, David; Ogaji, Daprim Samuel
Background: While patient satisfaction is a core index for the assessment of health quality, waiting time and payment mode in hospitals could influence outpatients' flow and as well as their level of satisfaction.Objective: This study compared the waiting time of insured and uninsured patients seeking general outpatient care in a tertiary hospital.Methods: A total of 166 insured and 166 uninsured ambulatory adult patients seeking outpatient services were recruited by systematic random sampling and followed through their consultation at the outpatient clinic. Descriptive and inferential statistics were conducted using the Statistical Package for Social Science (version 20.0) at a 5% alpha level and power of 80%.Results: There were more males (54.8%) among the insured and more females (53.0%) among the uninsured, but the difference was not statistically significant ( P = .153). There were significant differences in mean total idle time during outpatient visits (md = 65.7 min; 95% CI: 69.1, 162.8; P < .001) and total time spent (md=106.6 min; 95% CI: 204.8, 211.8; P < .001) in favor of insured patients. The time spent during the consultation was not significantly different (md = 0.8 min; 95% CI: 0.2, 1.7; P = .107). The insured patients were significantly more satisfied with the time spent waiting for nurses' and doctors' attention ( P < .001).Conclusion: Significant variations exist in the time spent and level of satisfaction with time spent by insured and uninsured ambulatory patients. Findings call for improving efficiency in patient flow management especially for uninsured patients attending outpatient clinics in public hospitals.